Interannual variability in net community production at the Western Antarctic Peninsula region (1997–2014). Issue 7 (10th July 2016) - Li, Zuchuan; Cassar, Nicolas; Huang, Kuan; Ducklow, Hugh; Schofield, Oscar
Abstract: In this study, we examined the interannual variability of net community production (NCP) in the Western Antarctic Peninsula (WAP) using in situ O2 /Ar‐NCP estimates (2008–2014) and satellite data (SeaWiFS and MODIS‐Aqua) from 1997 to 2014. We found that NCP generally first peaks offshore and follows sea‐ice retreat from offshore to inshore. Annually integrated NCP (ANCP) displays an onshore‐to‐offshore gradient, with coastal and shelf regions up to 8 times more productive than offshore regions. We examined potential drivers of interannual variability in the ANCP using an Empirical Orthogonal Function (EOF) analysis. The EOF's first mode explains ∼50% of the variance, with high interannual variability observed seaward of the shelf break. The first principal component is significantly correlated with the day of sea‐ice retreat (R = −0.58, p < 0.05), as well as the Southern Annular Mode (SAM) and El Niño Southern Oscillation (ENSO) climate indices in austral spring. Although the most obvious pathway by which the day of sea‐ice retreat influences NCP is by controlling light availability early in the growing season, we found that the effect of day of sea‐ice retreat on NCP persists throughout the growing season, suggesting that additional controls, such as iron availability, are preconditioned or correlated to the day of sea‐ice retreat. Key Points: ANCP in shelf and coastal regions is up to 8 times higher than offshore regions ANCP in the seaward of shelf break shows high interannual variability ANCP interannual variability is associated with sea‐ice dynamics and the SAM and ENSO climate indices